Chemobrain in blood cancers: How chemotherapeutics interfere with the brain's structure and functionality, immune system, and metabolic functions - Skurlova, M; Holubova, K; Kleteckova, L; Kozak, T; Kubova, H; Horacek, J; Vales, K (Medicinal research reviews, 2024)
Cancer treatment brings about a phenomenon not fully clarified yet, termed chemobrain. Its strong negative impact on patients' well-being makes it a trending topic in current research, interconnecting many disciplines from clinical oncology to neuroscience. Clinical and animal studies have often reported elevated concentrations of proinflammatory cytokines in various types of blood cancers. This inflammatory burst could be the background for chemotherapy-induced cognitive deficit in patients with blood cancers. Cancer environment is a dynamic interacting system. The review puts into close relationship the inflammatory dysbalance and oxidative/nitrosative stress with disruption of the blood-brain barrier (BBB). The BBB breakdown leads to neuroinflammation, followed by neurotoxicity and neurodegeneration. High levels of intracellular reactive oxygen species (ROS) induce the progression of cancer resulting in increased mutagenesis, conversion of protooncogenes to oncogenes, and inactivation of tumor suppression genes to trigger cancer cell growth. These cell alterations may change brain functionality, as well as morphology. Multidrug chemotherapy is not without consequences to healthy tissue and could even be toxic. Specific treatment impacts brain function and morphology, functions of the immune system, and metabolism in a unique mixture. In general, a chemo-drug's effects on cognition in cancer are not direct and/or in-direct, usually a combination of effects is more probable. Last but not least, chemotherapy strongly impacts the immune system and could contribute to BBB disruption. This review points out inflammation as a possible mechanism of brain damage during blood cancers and discusses chemotherapy-induced cognitive impairment.
Keywords: hematologické nádory; Hematologic Neoplasms; mozek; chemobrain; BBB; imunitní systém; Chemotherapy-Related Cognitive Impairment; Neoplasms; Brain; kognitivní porucha po chemoterapii; zvířata; Humans; neuroinflammation; nádory; chemotherapy; Immune System; blood cancer; lidé; Animals